Particle-in-cell simulations of intense laser-matter interactions, with a focus on light ion acceleration - Magnusson, Joel (My University, 2015)
In conventional accelerators the risk of electrical breakdown limits the electric fields used to accelerate charged particles to the order of 100 MV/m. As a result, the accelerators are required to be very long in order to achieve particle beams of very high energy. Owing to this, and with the advancement of lasers of ever increasing intensity and power, laser-driven plasma-based acceleration has become a field of intense study. This is mainly motivated by the fact that such accelerators can sustain acceleration gradients several orders of magnitude larger than conventional accelerators (fields of several TV/m have been measured), thus allowing the accelerator to be made correspondingly more compact. In this work we focus on light ion acceleration in the TNSA regime (Target Normal Sheath Acceleration). In doing so, we also investigate unphysical numerical effects in the code Picador, a purpose-built numerical tool specifically designed for large-scale 3D particle-in-cell plasma simulations and with unique capabilities of investigating ultra-intense laser-plasma interactions. Picador is further developed with tools to more easily identify new numerical issues and also for suppressing found numerical effects on TNSA simulation results. The issue of artificially charging the simulation boundary is shown to have little to no effect on TNSA simulations using Picador, given that the simulation region is sufficiently large. Furthermore, this size coincides well with the required size for acceleration saturation to occur and is shown to be feasible for 2D TNSA simulations with regards to computational costs. Furthermore, a number of numerical issues were identified, and eventually resolved, much through the use of a new module in Picador that simply tracks the total simulation energy. Alternative target designs for improving light ion beam energy and collimation are simulated and analysed. Results show that the beam energy can be greatly improved with nano-sized cones on the front target surface. It is further shown that a similar effect can be obtained by restricting the hot electrons from being transported away in the transverse (to the target normal) directions. Furthermore, simulations using nano-sized cones on the rear target surface, in an attempt at increasing the strength of the charge-separation field, have been carried out. However, it is shown that this completely ruins the collimation of the beam and without improving the beam energy, the structures presumably being too small to affect the charge-separation field for a sufficient amount of time.
Keywords: Materialvetenskap; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Fysik; Materials Science; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship; Physical Sciences